1992
DOI: 10.6028/nist.ir.4788
|View full text |Cite
|
Sign up to set email alerts
|

Development of characterization techniques for polyurethanes I. Characterization of SRM 1480, a low molecular weight polyurethane for SEC calibration

Abstract: The characterization of a pol 3 rurethane standard reference material, SRM 1480, is described. The weight-average molecular weight of SRM 1480 by light scattering was determined to be 4.7 x lO'* g rnole"^. The intrinsic viscosity of SRM 1480 in THF was also measured and found to be 43.8 mL/g. The Size Exclusion Chromatography (SEC) of SRM 1480 in THF as received in the bottle was found to exhibit concentration dependent peak positions, even at low concentrations. The addition of 0.01 moles per liter LiBr to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Additional studies on the degradation of SRM 1480 in DMAC were made by running the SEC after storing the solution for a known time. These studies, which are described in a previous report [ 1 ], showed a shift in the SEC peak only after the solutions were stored in the dark for more than a week.…”
Section: Estimation Of Degradation Rate By Light Scatteringsupporting
confidence: 63%
See 4 more Smart Citations
“…Additional studies on the degradation of SRM 1480 in DMAC were made by running the SEC after storing the solution for a known time. These studies, which are described in a previous report [ 1 ], showed a shift in the SEC peak only after the solutions were stored in the dark for more than a week.…”
Section: Estimation Of Degradation Rate By Light Scatteringsupporting
confidence: 63%
“…The effect of column loading and the addition of controlled amounts of water were studied to see their effect on this problem. None of these were effective in improving the shape or repeatability of the peak position as a function of concentration [1].…”
Section: Concentration Studiesmentioning
confidence: 97%
See 3 more Smart Citations